Liposomes Containing Nickel-Bis(dithiolene) Complexes for Photothermal Theranostics - Ciancone, Mathieu (Langmuir : the ACS journal of surfaces and colloids, 2019)
New thermosensitive liposomes with a phase transition at 42 °C, containing nickel-bis(dithiolene) complexes as efficient and stable photothermal agents, have been formulated and characterized. These liposomes are highly stable and keep their contents at 37 °C for more than 30 days. On the contrary, the mild hyperthermia generated by the nickel-bis(dithiolene) complex under 940 nm NIR irradiation allows for the fine controlled release of the liposome contents, making such liposomes highly suitable for on-demand drug delivery in the human body under NIR laser irradiation. These liposomes can also be directly used, as shown here, as nanoagents for photothermal therapy. In fact, strong cell death can be generated under laser irradiation in the presence of these photothermally active nanocargos containing less than 10% w/w of metal complex. We also demonstrate, for the first time, that nickel-bis(dithiolene) complexes are good photoacoustic agents, generating easily detectable ultrasonic signals directly proportional to the concentration of complexes and the used laser power